2012
DOI: 10.4236/fns.2012.31019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Essential (Ca, Fe, I, K, Mo) and Toxic Elements (Hg, Pb) in Brazilian Rice Grains and Estimation of Reference Daily Intake

Abstract: The levels of Hg and Pb (toxic elements) and Ca, Fe, I, K, Mo (essential elements) were measured in 44 Brazilian rice samples divided among white polished (W), parboiled white (PW) and parboiled brown (PB). Rice grains were ana- lyzed by inductively coupled plasma mass spectrometry (ICP-MS). Concentrations of toxic elements varied from 0.3 to 13.4 and 0.4 to 14.5 ng?g–1 for Hg and Pb, respectively. The values for essential elements were in the same range of those for rice produced in other countries. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
7
20
1
3
Order By: Relevance
“…A high mean level of 0.022 mg/kg ( n =  13) in the polluted area of China, was reported by Huang et al [5]. Also, the high Hg level ranged from 0.3 to 13.4 mg/kg ( n =  44) in rice was reported in Brazil [32].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…A high mean level of 0.022 mg/kg ( n =  13) in the polluted area of China, was reported by Huang et al [5]. Also, the high Hg level ranged from 0.3 to 13.4 mg/kg ( n =  44) in rice was reported in Brazil [32].…”
Section: Resultsmentioning
confidence: 81%
“…In recent years, several studies reported that the mean levels of Cd were no more than 0.1 mg/kg in common area of China [5], [30], [31]. However, high levels of Cd in rice ranging from 0.21 to 2.4 mg/kg were revealed in some contaminated sites of China [3], [32].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of recent studies on methylation in rice paddies have examined contaminated systems (Rothenberg et al 2014), which are beyond the scope of this paper. However, methylation has been found to occur in non-contaminated rice cultivation sites around the world including Brazil (da Silva et al 2010;Batista et al 2012;Silva et al 2012), China (Rothenberg et al 2011), and Spain (da Silva et al 2013). The use of stable isotope tracers recently confirmed that MeHg produced in saturated soils is subsequently observed in the plant's rice grains (Strickman and Mitchell 2017), suggesting that the prevalence of methylation in rice paddies is a significant concern due to its potential to cause mercury poisoning directly through a common staple food source.…”
Section: Inundated Environmentsmentioning
confidence: 99%
“…In agricultural crops the main sources of heavy metal contamination are irrigation with contaminated water, metal based pesticides, industrial emissions, fertilizers and transportation, harvesting process, storage, and/ or sale of crops 8,9,10 . As rice is one of the major agricultural products on the national and international market 11 , during last decades many researchers have reported heavy metal concentrations, especially for Pb,Cd, Cr and the other elements in rice grains from various countries such as Iran, India, China, South and North Korea, Taiwan and Turkey 7,13,14,15,16,17 . Daily consumption of rice in Asia countries ranges between 158-178 g/ person-day 7,18,19 Iranian people eat an average of 40 kg of rice every year 20 .Although Iran is eleventh producer of rice at the world with an annual production 2600000 tons in 2010, during the last years the demand for rice has considerably been increased in comparison with its production, as a result, currently Iran is known as one of the largescale importer of rice countries 21 .…”
Section: Introductionmentioning
confidence: 99%